Occurrence and Behaviour of White-Tailed Eagles Haliaeetus albicilla in Great Cormorant Phalacrocorax Carbo Sinensis Colonies in Countries around the Baltic Sea - Bregnballe, Thomas; Tofft, Jesper; Kotzerka, Jana; Lehikoinen, Aleksi; Rusanen, Pekka; Herrmann, Christof; Krone, Oliver; Engström, Henri; Rattiste, Kalev; Reich, Jürgen; Kouzov, Sergey A. (Netherlands Ornithologists' Union, 2022)
The recovery of the Baltic White-tailed Eagle Haliaeetus albicilla population since the 1980s is a conservation success story. However, the re-establishment of this predator in coastal and lake areas appears to affect Great Cormorants Phalacrocorax carbo during the breeding season. We collated published and unpublished records of White-tailed Eagle occurrence and interactions with Cormorant colonies as well as records of Cormorant anti-predator responses and effects on Cormorant breeding performance. We found evidence for immediate direct effects (mainly kleptoparasitism, predation of eggs and offspring) and indirect effects (facilitating nest predation by mainly gulls and corvids). Repeated disturbance from hunting White-tailed Eagles was also inferred to trigger changes in selection of nest sites, to cause complete abandonment of colonies and lead to regional redistributions of breeders. However, there are also observations of ‘unproblematic’ coexistence with White-tailed Eagles breeding inside Cormorant colonies. There is some evidence to suggest that nesting opportunities for Cormorants may become further restricted as White-tailed Eagle numbers continue to increase, and we argue that this – in some regions – will impose limitations on the distribution and size of breeding populations of Cormorants.